The method of historiography of Muhammad bin Muhammad Al-yamani in the historiographic discourse of the Ismailis - Ali Babaei Siab (تاریخ نگری و تاریخ نگاری, 2023)
Mohammad ibn Mohammad al-Yamani was one of the authors at the court of al-Aziz Billah, the fifth Fatimid caliph. The short treatise Sirat al-Hajib is the only surviving text by him that has historical content. This treatise, commissioned by the caliph of the time, recounts the events surrounding the Fatimid rise to power between 286 and 297 AH, based on the narratives of Ja’far ibn Ali al-Hajib, the personal advisor of Ubaydullah al-Mahdi. An eleven-year period in Fatimid history that began with the proclamation of the Imamate by Ubaydullah al-Mahdi and ended with the establishment of the Fatimid government in Raqqada. This treatise is the only Fatimid source that specifically describes an ambiguous period of Fatimid history from an internal organisational perspective. It seems that the treatise Sirat al-Hajib can be assigned to the Isma'ili historiographical discourse, as it exhibits characteristics of a sacred historiography with a theological approach, a combined method in narrating events, and reliance on eyewitness accounts and reliable sources of the Isma'ili historian. The research method in this article is qualitative content analysis and data collection based on library research.